Revisiting Islamic Da’wah: Principles and the Prophetic Approach to Religious Communication - Abdulsalam, Daud Olalekan (Universitas Muhammadiyah Surakarta, 2025)
Da’wah, or Islamic propagation, is a core religious obligation grounded in the Qur’an and Sunnah. It invites humanity to Islam and guides believers toward righteousness, following the example of Prophet Muhammad (peace be upon him). Linguistically meaning “call” or “invitation,” Da’wah includes spreading Islamic teachings, encouraging good, and discouraging wrongdoing. In contemporary contexts, it is conducted through personal interaction, community engagement, digital platforms, and interfaith dialogue, aiming to share Islam’s message of peace, purpose, and submission to Allah. This paper explores the divine purpose of Da’wah, its components, the message, the caller, and the called and the methodological principles drawn from Qur’an 16:125: wisdom (al-hikmah), good exhortation (al-maw‘izah al-hasanah), and gracious argumentation (al-jidal bil-lati hiya ahsan). Using analytical and historical methods, it highlights the universal nature of Da’wah, its distinction from other religious invitations, and the essential qualities of the caller (da‘i). The study affirms that Da’wah is a holistic system involving the subject (al-mawdu’), the caller (ad-da’iyah), and the audience (al-mad‘uww). It concludes that effective Da’wah requires wisdom, kindness, and strong character, rooted in Prophetic methodology. It recommends structured training, ethical communication, community-based programs, digital strategies, and increased accessibility through translated classical works.